Clinical Approach to Children with Low Appetite - Fatih Ünal (Güncel Pediatri)
Appetite is a conscious desire for food and it is regulated mainly by the gastrointestinal system, pancreas and adrenal glands. Poor appetite is a common problem in childhood. For assessment, history of development, nutrition and family are important. Poor appetite may also be a symptom of feeding disorders. Even though the etiology of feeding disorders may be classified as organic or functional, it indeed reflects the complex interaction of biological, behavioral and social factors. Personal, familial, economic and sociocultural factors may affect appetite. In this review, approaches to a child with low appetite who presents a difficult problem for his/her family and doctor are discussed in the light of recent literature. (Journal of Current Pediatrics 2011; 9: 79-84)